Semi-Automatic Medical Syringe Pump Development: Interface, Control, Alarm, and Feedback - Kevin Nicholas Tanex; Megantara Pura (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2022)
The syringe pump is used to inject liquids for a long period of time and on a small volume scale. The presence of air inside the hose whilst injection into the human body is dangerous. Early detection can be done using a bubble sensor. The SPICAF is equipped with a gearbox capable of injecting long-term injections on a small scale, and a bubble sensor capable of detecting air by comparing light intensity on a clear hose which automatically notifies the user if dangerous conditions occur. The SPICAF is successfully designed, developed, and tested to WHO specifications. It’s injection has 98% accuracy and is able to detect air bubbles properly.